Intercropping Impact on Weed Dry Matter, Soil C/N content and Sugarcane (Saccharum officinarum) Productivity - Bassey, M.S. (e-Proceedings of the Faculty of Agriculture International Conference, 2023)
The effects of intercropping on weed dry matter, soil C and N, and sugarcane productivity were investigated at Badeggi, Nigeria in 2016 and 2017. The results revealed that application of Sugarcane + Groundnut intercropping produced lower weed dry matter comparable to Sugarcane + Soybean intercropping which significantly increased growth and yield attributes of sugarcane. Application of Sugarcane + Groundnut intercropping, resulted in a comparable germination count, Tiller count, plant and stalk height with Soybean intercropping. It generated taller plants and stalks, more girth, brix content, millable cane, stools and cane yield. Similarly, Sugarcane + Groundnut intercropping and Soybean intercropping produced comparable stalk height and brix content. In conclusion, application of Sugarcane + Groundnut intercropping or Soybean intercropping effectively controlled weeds, increased Soil C and N, plant and stalk height, girth, brix content, millable cane, stools and cane yield of sugarcane.